Multimodal imaging study of pancreatic myeloid sarcoma: a case report and literature review - Hu, Xianwen; Li, Wenxin; Tang, Jinyan; Li, Dandan; Wang, Pan (Frontiers in Oncology, 2023)
Myeloid sarcoma (MS) is a rare extramedullary parenchymal tumor composed of immature myeloid cells, occurring mainly in the lymph nodes, skin, soft tissue, testicles, bones, peritoneum, and gastrointestinal tract, and rarely in the pancreas. Herein, we report the case of a 68-year-old female patient who visited our hospital for medical assistance due to acute abdominal pain. Abdominal computed tomography (CT) and magnetic resonance imaging showed a mass approximately 8 cm in diameter in the pancreatic tail, which was suspected to be a malignant tumor. To further assess the presence of distant metastases, the patient underwent fluorine-18-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET)/CT, which revealed an increased 18 F-FDG uptake in the corresponding lesions. Subsequently, the patient underwent surgical treatment, and postoperative pathology and immunohistochemistry revealed that the mass was MS. Moreover, we reviewed the clinical features, imaging findings, and histopathology of the pathologically confirmed pancreatic MS in published literature.